2018
DOI: 10.14419/ijet.v7i4.9.20628
|View full text |Cite
|
Sign up to set email alerts
|

Role of Political Education in Improving Public Participation in Election: The Case ofWest Sumatera Governor Election

Abstract: This article describes the role of political education to improve public participation in the election of West Sumatra governor. The governor election is expected to be able to raise the level ofoptimism in order to improve the leadership qualities of local government, and the spirit of political education for citizen. This study applied descriptive qualitative method by using interviews and documentations as research instruments. Based on the documentation instrument, it showed the statistics of permanent vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Political literacy is defined as the ability of an individual to make political choice and to give opinion, to be aware of his/her rights, and to have knowledge on state governance, regulations, and autonomous aspects in life [1]. Political literacy plays an important role in a democratic process, and is acquired through political education.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Political literacy is defined as the ability of an individual to make political choice and to give opinion, to be aware of his/her rights, and to have knowledge on state governance, regulations, and autonomous aspects in life [1]. Political literacy plays an important role in a democratic process, and is acquired through political education.…”
Section: Introductionmentioning
confidence: 99%
“…Democratically-elected goverment shall be formed if the voters can exercise their respective individual rights by voting freely and without any duress from any party whomsoever [2], [1]. Election results in Indonesia in 2019 showed that the participation level of the voters reached 81.93%, which was considerably high, in which the number of legitimate votes for legislative election (DPR) amounted to 139.970.810 votes, and for presidential election amounted to 154.257.601 votes [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations